A Comparative Proteomic Analysis of Responses to High Temperature Stress in Hypocotyl of Canola (Brassica napus L.) - Ismaili, Ahmad; Salavati, Afshin; Pour Mohammadi, Payam (Protein and Peptide Letters, 2015)
High temperature stress, especially on the early season of plant growth stages, is an agricultural problem in many areas in the world. A temporary or continually high temperature leads to a set of morphological, biochemical and physiological changes in plants, which consequently reduces the plant growth and development and finally may cause a severe reduction in economic yield. The main goal of this study was to assess plant response to high temperature stress (HTS) in early seedling of canola. This study is the first experiment on the effect of heat stress on proteome of canola. In the present research, a proteomics approach was used to evaluate the effects of high temperature stress, including 45 °C day/34 °C night for 2, 6 and 12 hour, on early seedling stage (2-day old) of canola. Proteins were isolated from hypocotyl and separated by two-dimensional polyacrylamide gel electrophoresis. Out of 381 protein spots, 28 and 34 proteins were significantly down- and up-regulated, respectively. The trend of mRNA expression for sucrose binding protein, a scorbate peroxidase and triosephosphateisomerase, was in accordance with their trend at translation level. Results of this study suggest that the up-regulation of proteins involved in cellular traffic, energy and metabolism, and down-regulation of some proteins involved in disease and defense, protein synthesis and signal transduction could be the main reason of physiological and morphological responses to high temperature stress. The observed increases in the level of ascorbate peroxidase protein and mRNA expression in canola hypocotyl in response to HTS suggests that ascorbate peroxidase is a short term high temperature stress response protein and is thus a candidate for gene modification strategies aimed at producing high temperature canola varieties. These results also suggest that the up regulation of protein involved in energy and metabolism in response to the heat stress can use most of nutritive reserves in seedling of canola and might explain the reduced growth of canola in heat stress conditions.
Keywords: hypocotyl